Chemoenzymatic Formal Total Synthesis of Pancratistatin from Narciclasine-Type Compounds via Myers Transposition: Model Study for a Short Conversion of Narciclasine to Pancratistatin - Lapinskaite, Ringaile; Ghavre, Mukund; Rintelmann, Chelsea L.; Bedard, Korey; Dela Paz, Helen E.; Hudlicky, Tomas (Synlett, 2017)
A formal total synthesis of pancratistatin was accomplished by conversion of advanced intermediates, used in the synthesis of narciclasine, to pancratistatin precursors via Myers’ reductive transposition as the key strategic step. The synthesis began with the whole cell fermentation of m-dibromobenzene with JM109(pDTG601a), a recombinant strain that over-expresses toluene dioxygenase, which provided the corresponding cis-dihydrodiol 16 as a single isomer with complete optical purity. The key reductive transposition of the allylic alcohol 8a to olefin 9a allowed for further installation of the C-1/C-2 trans-diol, required for the pancratistatin scaffold, through the introduction of a cyclic sulfate and its subsequent opening. The formal synthesis of pancratistatin was accomplished in 14 steps (12 operations) from commercially available m-dibromobenzene. Experimental and spectral data are provided for all new compounds.
Keywords: narciclasine; pancratistatin; toluene dioxygenase; enzymatic dihydroxylation of arenes; reductive transposition of allylic alcohols